Determining Factors of Dividend Policy In Indonesia - Bertuah, Eka; Maskat Baherans, Dede; Aria Dewi Siskawati, Sinta; Winarso, Eddy (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to find out financial ratios that could be the determinant factors of dividend policy in manufacturing companies listed on the Indonesia Stock Exchange during the period 2015 to 2017. Purposive sampling was used in sampling techniques with the acquisition of 118 companies as research samples. The data analysis technique used in this study is the discriminant test with the Mahalanobis Stepwise method. The results of this study indicate that ROA, NPM, Firm Size, and Current Ratio can distinguish significantly between companies that distribute dividends with companies that do not distribute dividends. Those four ratios are ranked according to their discriminative power. ROA came out as strongest factor, followed by NPM, Firm Size. While Current Ratio is the weakest factor. The higher those four financial ratios, the more likely a company is distributing dividends. The classification results also show that 41 companies tend to distribute dividends, 55 companies tend not to distribute dividends, 22 other tendencies are not determined. This study provides evidence that manufacturing companies in Indonesia are more following what is hypothesized by signaling theory and life cycle theory.